The COVID-19 pandemic effects on the financial performance of Brazilian listed companies - Avelar, Ewerton Alex; Orefici, Jacqueline Braga Paiva; Borges, Sergio Louro; Campos, Octávio Valente; Ferreira, Priscila Oliveira (Revista de Administração da UFSM, 2022)
Purpose – The study aimed at analyzing the effects of the COVID-19 pandemic on the financial performance of Brazilian public companies listed on Brasil, Bolsa, Balcão (B3) in 2020. Design/methodology/approach – It is a quantitative and descriptive research. A final sample of the study consisted of 158 companies that simultaneously provided the quarterly data of interest (economic-financial and operational) on both the B3 website and the Economática® Platform, from 2019 to 2020. In order to analyze data, we employ the following techniques: content analysis, descriptive statistics, Kolmogorov-Smirnov test, Kendall correlation coefficient, Kruskal-Wallis test, Wilcoxon test and multiple regression. Findings – The results indicated the expected effects on the companies’ financial performance in the first two quarters of 2020: (1) reduction in market value and profitability; and (2) increase in activity cycles and indebtedness. In the following quarters, there was a reversal of these effects, with different proportions for companies in different sectors. Originality/value – It contributes to the literature on corporate finance in different aspects: (a) it presents a broad analysis of the effects of the COVID-19 pandemic on the different economic and financial dimensions of companies from different sectors; (b) discusses not only the effects of the pandemic, but also the reactions of companies and the economic and financial implications of these reactions; (c) analyzes external and internal information to companies to support conclusions; and (d) as it covers all quarters of 2020, it makes it possible to analyze the evolution of the impacts of the pandemic over the period.